Growth response, economic indices, blood profile, and organ weight of pigs fed rejected cashew kernel meal from weaner to growing phase - Ojediran Taiwo K.; Aniyikaye Sarah A.; Akinola Rukayat O.; Emiola Isiak A. (Biotechnology in Animal Husbandry)
Growth response, economic indices, blood profile, and organ weight of pigs (large white x landrace, n=40, average initial weight = 8.67±0.3kg) fed rejected cashew kernel meal RCKM) were examined from the weaner to growing phase. They were randomly allotted to four groups designated as diet 1, 2, 3, and 4 containing 0%, 5%, 10% and 15% rejected cashew kernel meal respectively in a completely randomized design for eighty-four days. Feed intake differs significantly (P<0.05) across the groups. Pigs offered 5% rejected cashew kernel meal had the highest feed intake with a decreasing trend across those given rejected cashew kernel meal. All economic indices were significant across the groups (P<0.05). Moreover, the heart weight was significantly influenced (P<0.05) by the experimental diet. Pigs fed with 15% RCKM had a significantly higher (P<0.05) heart weight compared with those fed other diets (P<0.05). From the outcome of this investigation, it can therefore be concluded that dietary inclusion of RCKM up to 15% did not trigger any deleterious effects in pigs in terms of growth performance, blood profile, reduced feed cost, increased profit, and economics of gain thus RCKM was well tolerated by the pigs without adverse physiological effects, supported optimal growth, health, and wellbeing of pigs from weaner to grower phase.